Smart Sensor Necklace Buoy / Ahmad Syafiee Abd Rahim ... [et al.] - Abd Rahim, Ahmad Syafiee; Mohd Ziyad, Mohamad Aidilziyad; Omar, Muhammad Fakhrulradzi; Raduan, Muhammad Sharul; Mohd Yusuff, 'Aqilah; Mohd Zaid, Nur Sahirah; Mohammad Ros, Siti Nur Liyana (2022)
Nowadays, people are concerned about drowning rates across the country. Our Buzz Buoy will provide buoyancy technology that uses sensors, manual triggers, and floating cushions. We can reduce the rate of children drowning while doing water activities. This product is suitable for all ages because of the occurrence of drowning regardless of age. Users only need to wear the Buzz Buoy by placing it around their neck like a chain around their neck. Our main target is those with small children. This is because the drowning rate is highest at the age of a child. Furthermore, we strive to deliver the greatest experience for our users in terms of safety products with our Safety Smart Sensor Necklace Buoy. The technology employed is a wireless remote control that can be used over a long distance. Furthermore, because our products use wireless technology, they require a battery to connect. Customers nowadays are concerned not only with the product's market quality, but also with its price, function, and status. For example, if the price is high and the consumer cannot afford to purchase the goods, the likelihood of the buyer rejecting the goods is significant. Thus, we are inspired to satisfy customers' wishes to make the product affordable for them to buy and also to achieve good functionality with the product. This Buzz Buoy has functions and advantages not found in today's common buoys, thus providing a competitive advantage over more established competitors.